Mechanical Action of Inhomogeneously Polarized Optical Fields and Detection of the Internal Energy Flows. (15th October 2011) - Bekshaev, A. Ya.; Angelsky, O. V.; Sviridova, S. V.; Zenkova, C. Yu.
Abstract : We analyze numerically correspondence between the mechanical action, experienced by a spherical microparticle, and the internal energy flows in the light field incident on the particle. The inhomogeneous incident field is modelled by superposition of two plane waves; the mechanical action is calculated via the Mie theory for dielectric and conducting particles of different sizes and optical properties. It is shown that both spin and orbital components of the field momentum can produce the mechanical action whose value and sign depend on many additional details of the field-particle interaction. Besides, forces that are not associated with any sort of the energy flow (e.g., the gradient force owing to the inhomogeneous intensity and the polarization-dependent dipole force emerging due to inhomogeneous polarization) can strongly modify the observed mechanical action. The polarization-dependent mechanical action on particles can be treated as a form of the spin-orbit interaction of light.